THE BRAZILIAN GROUNDWATER LAW - de Fernandes, Luciana Cordeiro Souza; Fernandes, Alexandre Martins [UNESP]; Cerezini, Monise Terra; Saito, Carlos Hiroo (Research Publishing Services, 2023)
Groundwater is typically the least known or understood part of the hydrological cycle in water resource management. Aquifers are the primary regulator of freshwater resources in the environment. Water crises around the world have taught us that water security problems are interconnected, and their solution depends on our understanding of the hydrological and biogeochemical cycles involved, as well as the interdependence of the different components with human behavior and socio-economic activities. These solutions need to be built in a collaborative interdisciplinary manner, including relevant economic, social, regulatory law, and governance aspects. Therefore, a regulatory law, a groundwater law is an important instrument for soil and aquifer management for the protection, prevention, and quality of groundwater. In Brazil, the constitutional competence to manage aquifers, present in the Brazilian Constitution of 1988, determines that groundwater be considered an asset of the states so that it can be managed through legal instruments and specific laws. However, only with the action of the municipalities, incorporating the areas of aquifer recharge in their laws of use and territorial organization, such protection will be achieved.
Keywords: aquifer recharge areas; environmental law; governance; legal integration; protect aquifers